Survival strategies among informal economy businesses: the case of small maize millers in Zambia - Mwango, Mutale (African Studies, 2024)
This study explores whether the informal sector survives in a competitive environment. It focuses on informal maize millers in an industry dominated by large-scale milling firms. The study was guided by a mixed methodology for data collection and analysis. This entailed the use of a case study design which facilitated the use of detailed, multi-faceted investigations of intricate issues in their real-life settings. Specifically, a customer survey and interviews with policy experts, informal millers, activists, and participant observations were used to collect data on the practices of informal maize millers' survival in a competitive environment. Primary data were complemented by use of secondary sources, which included various documents from the public sector, civil society and international organisations in the quest to have a deeper understanding of the informal sector. Present studies about informal maize millers in Zambia provide limited attention to understanding practices of informal sector establishments. This study used the structuralist theory to explain how informal maize millers operate in a competitive environment. Structural theory focuses on the patterns of relationships among social actors. The structuralist theory is used to understand the connection that occurs between formal and informal sector activities because it takes the informal sector as being connected to the formal sector. The study applied the structuralist theories to the informal milling sector in Zambia by demonstrating interlinkages between large formal firms and market needs through servicing the needs of impoverished consumers in townships who depend on such firms and by supplying niche products to state institutions and supermarkets that were not supplied by large firms. The study identified and discussed different factors which enable informal millers to survive the competition from big commercial milling companies. The study also found that informal maize millers cater for different categories of customers including low, middle- and high-income customers. This study contributes to the body of knowledge by making an empirical contribution to understanding the survival of informal maize millers in an industry dominated by large-scale milling firms. Furthermore, from the insights, the study also develops a framework for survival and competitiveness showing pathways for informal maize millers. The study makes the argument that informal maize millers survive competition by adopting various survival strategies, such as choosing to remain informal, diversifying the maize products, and offering lower prices for maize meal.